Features of cardiometabolic disorders in obesity on the example of the children’s population of the Rostov region - O. V. Bocharova; E. D. Teplyakova; T. P. Shkurat; G. V. Karantysh; Alaa Hashim Abd Ali (Медицинский вестник Юга России, 2022)
Objective: to study the features of the blood lipid profile in obese children and adolescents, depending on the presence of insulin resistance, endothelial dysfunction and minimal diastolic dysfunction of the left ventricle. Materials and methods: the study involved 370 obese children and adolescents from 7 to 17 years of age (the main group) with a body mass index BMI > 30, the control group consisted of 123 children of the same age without obesity. Methods: clinical, paraclinical (biochemical blood test, blood pressure measurement, functional diagnosis of endothelial dysfunction, assessment of minimal diastolic dysfunction). Results: cardiometabolic disorders in obesity in childhood and adolescence are accompanied, first of all, by hypertriglyceridemia, which entails further violations of the lipid profile. There was also a positive correlation between changes in insulin and triglyceride levels in children and adolescents with obesity and endothelial dysfunction, as well as in patients with HOMA IR 3.2 and a combination of endothelial dysfunction and minimal dysfunction. Conclusions: based on the study of the nature of lipid spectrum disorders in obese children and adolescents and the presence of signs of endothelial dysfunction and/or minimal left ventricular dysfunction, it was concluded that obesity at this age is more often accompanied by minimal left ventricular diastolic dysfunction or a combination of endothelial dysfunction and left ventricular dysfunction. The development of insulin resistance leads to an increase in the combined pathology (ED and MDLj). Hypertriglyceridemia, which is associated with high levels of insulin and presumably determines the development of insulin resistance, plays an important role in the development of cardiometabolic disorders in obesity in childhood and adolescence.